APLIKASI PENGENALAN IRIS MATA MENGGUNAKAN METODE HOUGH TRANSFORM DAN GABOR WAVELET - Fransisca Joanet Pontoh; Fransiscus Xaverius Senduk; Inggrit E. G. Pondaag (JURNAL ILMIAH INFORMATIKA, 2021)
Biometric system is a development of the basic method of identification system by using the characteristics of humans as it’s object. These include face, fingerprints, signature, palms, iris, ears, sounds even DNA. Face recognition is one of the identification techniques in biometrics that uses part of the face as its parameter. One of the biometric parts of face is Iris. Iris is a unique part of the eyes, this is because the pattern of the somebody eyes will be quite different from the other, even genetically identical twins have different iris patterns. This research will use the Hough and Gabor method to perform iris recognition. The  results show that the application has succeeded in recognizing the selected eye image if the eye image is registered in the database.